COVID-19 outbreak: Consumer impulsive buying behavior towards personal safety and healthcare products - Muhammad Danish Habib; Nadia Ashraf (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
The global escalation of COVID-19 in 2020 has altered the consumption patterns of consumers. The research on impulsive buying during a pandemic is understudied and requires more scholarly intentions. This study addresses this gap by utilizing the reflections of well-known theoretical lenses: affect theory, the health belief model, and social exchange theory in the context of impulsive buying attitudes toward personal safety and healthcare products. The research model hypothesized the positive association between emotional, cognitive, and behavioral aspects. A total of 407 online buyers were recruited through an online cross-sectional survey. The empirical model was examined by using a method of covariance-based structural-equation modeling. Data was analyzed by using SPSS 26 and AMOS. The study findings showed a significant positive association between emotional, cognitive, and behavioral aspects. Negative and positive appeals significantly drove consumer perceptions about threats, benefits, and costs. The study results supported that cognitive aspects were associated considerably with impulsive buying behavior toward safety care products. The study findings significantly affect regulators, academics, and practitioners interested in developing regulations and strategies during pandemic situations.
Keywords: 330; COVID-19; health belief model; affect theory; social exchange theory; impulsive buying behavior; personal safety; online buyers; health care products; Pakistan